Anticipating the financial crisis: evidence from insider trading in banks. (17th November 2020) - Akin, Ozlem; Marín, José M; Peydró, and José-Luis
Abstract: Banking crises are recurrent phenomena, often induced by excessive bank risk-taking, which may be due to behavioural reasons (over-optimistic banks neglecting risks) and to conflicts of interest between bank shareholders/managers and debtholders/taxpayers (banks exploiting moral hazard). We test whether US banks' stock returns in the 2007–8 financial crisis are associated with bank insiders' sales of their own bank's shares in the period prior to 2006Q2 (the peak and reversal in real estate prices). We find that top-five executives' sales of shares predict bank performance during the crisis. Interestingly, effects are insignificant for the sales of independent directors and other officers. Moreover, the top-five executives' impact is stronger for banks with higher exposure to the real estate bubble, where a one standard deviation increase of insider sales is associated with a 13.33 percentage point drop in stock returns during the crisis period. Finally, even though bankers in riskier banks sold more shares (furthering their own interests), they did not change their bank's policies, for example, by reducing bank-level exposure to real estate. The informational content of bank insider trading before the crisis suggests that insiders knew that their banks were taking excessive risks, which has important implications for theory, public policy and the understanding of crises, as well as a supervisory tool for early warning signals.